Surgical Technique And Clinical Implications Of Transcatheter Aortic Valve Bioprosthesis Explantation - Tsiouris, Athanasios (2024)
There has been a worldwide rapid adoption of transcatheter aortic valve replacement (TAVR) as an alternative to surgical aortic valve replacement (SAVR) for patients with severe aortic stenosis. Currently, more TAVR explants with SAVRs are performed than TAVR-in TAV. TAVR explantation is a technically hazardous procedure mainly due to significant aortic neo-endothelialization which incorporates the TAVR valve. Surgical techniques for TAVR explantation are not well established and surgeon experience at present is limited. In this manuscript, we describe our technique for surgical explantation of transcatheter aortic bioprosthesis. Familiarity with the procedure and its clinical implications is essential for all cardiac surgeons.